Penerapan Model Pembelajaran Inkuiri Terbimbing untuk Meningkatkan Keterampilan Berpikir Kritis dan Hasil Belajar Peserta Didik - Safni Yunia; Hasanuddin Hasanuddin; Salma Samputri (Universitas Negeri Makassar, 2026)
This study aims to find out: 1) The level of critical thinking skills and learning outcomes of students before and after the application of the guided inquiry learning model. 2) Improvement of critical thinking skills and student learning outcomes before and after the application of the guided inquiry learning model. 3) Significant improvement in students' critical thinking skills and learning outcomes before and after the implementation of the guided inquiry learning model. This research is a pre-experimental research with a One Group Pretest- Posttest Design research design. The research population is all students of the State Junior High School 2 Pattallassang class consisting of 7 classes totaling 246 students. Sampling was done through the purposive sampling method from class VIII.1 with a total of 32 samples. The data collection technique in this study is by providing pretest and poststest. Data analysis was carried out using descriptive and inferential analysis. The results showed that: 1) The level of critical thinking skills and learning outcomes of students scored an average critical thinking skill of 14.28 and learning outcomes of 6.90. After application with an average score of 16.83 critical thinking skills and learning outcomes of 6.80 were in the low category. 2) Improvement of students' critical thinking skills obtained with an average N-Gain of critical thinking skills of 0.09 and an average N-Gain of learning outcomes of -0.06, in the low category. 3) There is a significant increase in critical thinking skills, this can be seen from the data of the t-test results of critical thinking skills have a significant value of 0.03, this means that H0 is rejected and H1 is accepted. And the Learning Outcomes did not significantly increase.